NATURAL AND ARTIFICIAL RADIOACTIVITY IN IMPORTED FISHERY PRODUCTS - R. Cavallina; A. Nardoni; M.C. Campagna (Italian Journal of Food Safety, 2013)
Considering the growing public concern over marine environmental quality, a program of monitoring radionuclids in imported fishery products has been established. The analyses have been performed by gamma spectrometry allowing the rapid detection of many artificial radionuclides such as 137Cs, 134Cs and 40K. The data obtained show Cs radionuclides levels within expected limits. The detection of natural radionuclide K showed different levels in the same fishery product as they came from different sea areas.